2017
DOI: 10.1016/j.placenta.2017.01.125
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the placental BCRP/ABCG2 transporter in response to hypoxia signaling

Abstract: Introduction The BCRP/ABCG2 efflux transporter protects the developing fetus by limiting the transplacental transfer of drugs and chemicals and prevents the apoptosis of trophoblasts. The purpose of this study was to determine whether hypoxia-related signaling alters placental BCRP expression and function in vitro and in human pregnancies. Methods Human BeWo choriocarcinoma cells were treated with the hypoxia mimetic, cobalt chloride (CoCl2), or 3% oxygen for 24-48 h. Activation of HIF-1α signaling and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Chemosensitivity of cancer cells also involves efflux ABC transporter-mediated mechanisms (Choi and Yu, 2014). In agreement with the role of NRF2 in drug resistance, NRF2 has been demonstrated to regulate the expression of many ABC transporters, including ABCB6, ABCC1-5, and ABCG2, which may differ due to the differences in types of cells with variable levels of expression and/or distinct regulatory pathways (Adachi et al, 2007;Aleksunes et al, 2008;Malhotra et al, 2010;Singh et al, 2010;Xu et al, 2010;Chorley et al, 2012;Canet et al, 2015;Jeong et al, 2015;Francois et al, 2017). Through interfering NRF2 with bioengineered NRF siRNA, the present study revealed a consequent reduction of ABCC3 expression in 143B cells as well as the suppression of ABCC4 and ABCG2 in MG63 cells, supporting the role of NRF2 in the regulation of ABC transporter expression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Chemosensitivity of cancer cells also involves efflux ABC transporter-mediated mechanisms (Choi and Yu, 2014). In agreement with the role of NRF2 in drug resistance, NRF2 has been demonstrated to regulate the expression of many ABC transporters, including ABCB6, ABCC1-5, and ABCG2, which may differ due to the differences in types of cells with variable levels of expression and/or distinct regulatory pathways (Adachi et al, 2007;Aleksunes et al, 2008;Malhotra et al, 2010;Singh et al, 2010;Xu et al, 2010;Chorley et al, 2012;Canet et al, 2015;Jeong et al, 2015;Francois et al, 2017). Through interfering NRF2 with bioengineered NRF siRNA, the present study revealed a consequent reduction of ABCC3 expression in 143B cells as well as the suppression of ABCC4 and ABCG2 in MG63 cells, supporting the role of NRF2 in the regulation of ABC transporter expression.…”
Section: Discussionmentioning
confidence: 86%
“…Bioengineered NRF2-siRNA Enhances Chemosensitivity Bioengineered NRF2-siRNA Modulates the Expression of NRF2-Regulated ABC Transporters in Human OS Cells. Recent studies have also demonstrated the role of NRF2 in the regulation of efflux ABC transporters (Adachi et al, 2007;Aleksunes et al, 2008;Malhotra et al, 2010;Singh et al, 2010;Chorley et al, 2012;Canet et al, 2015;Francois et al, 2017). Therefore, we assessed the influence of BERA/NRF2-siRNA on the mRNA levels of five ABC transporters, ABCC1-4/MRP1-4 and ABCG2/breast cancer resistance protein, in human OS cells.…”
Section: Resultsmentioning
confidence: 96%
“…40 Interestingly, a downregulation of BCRP in response to low oxygen levels has been reported in BeWo cells. 41 Thus, the observed downregulation of BCRP could occur due to simultaneous and additive events rather than through a single pathway. Although hypoxia is more commonly associated with a reduction in VEGF expression, 42 it has been reported that low oxygen tension caused an increase in transcript levels of VEGF along with increased BCRP in human placental explants, which further supports involvement of angiogenic factors.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, compared to placental explants from term placentas experimentally exposed to low oxygen tension for 24 and 48 hours, the development of placentas from the first trimester occurs in hypoxic conditions. However, in a recent study [50], western blot analysis also showed decreased expression of BCRP in microvillous membrane of placentas from women who gave birth at a high altitude, suggesting down-regulation of BCRP under hypoxic conditions. Previously, Krishnamurthy and colleagues showed that hypoxia upregulated expression of BCRP in mouse hematopoietic stem cells and that this upregulation is regulated by the hypoxia-inducible transcription factor complex HIF-1 [51].…”
Section: Discussionmentioning
confidence: 99%